2020
DOI: 10.1177/0733464819898643
|View full text |Cite
|
Sign up to set email alerts
|

Using Concept Mapping Methods to Define “Healthy Aging” in Anchorage, Alaska

Abstract: This exploratory research project captured a multidimensional model of healthy aging in Anchorage, Alaska, by utilizing the Concept Mapping (CM) methodology with a sample of 53 older adults (aged 55+), aging advocates, public health professionals, and senior service providers. Multidimensional scaling and cluster analyses were conducted to map the relationship between 100 aspects of healthy aging, resulting in 12 distinct concepts of healthy aging. Study participants identified both lifestyle factors and aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Results indicated wide-ranging commonalties but important variations; service providers rated religion and spirituality as more important than the scholars did. Likewise, Howell et al (2021) used concept mapping to developed a locally contextualized definition of healthy aging among older adults living in the circumpolar North and in a later study, they asked participants to rank key components by importance and feasibility. Howell et al (2020) found that older adults ranked environmental features such as sidewalks with curb cuts as important, but less feasible than psychological and behavioral aspects of healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated wide-ranging commonalties but important variations; service providers rated religion and spirituality as more important than the scholars did. Likewise, Howell et al (2021) used concept mapping to developed a locally contextualized definition of healthy aging among older adults living in the circumpolar North and in a later study, they asked participants to rank key components by importance and feasibility. Howell et al (2020) found that older adults ranked environmental features such as sidewalks with curb cuts as important, but less feasible than psychological and behavioral aspects of healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Concept mapping is a way of identifying essential components of a concept and then assembling these in a way that can help in conceptual understanding. As a study design, it has been used in many areas including hand hygiene [ 29 ], intimate partner violence [ 30 ], gender and higher education [ 31 ], healthy aging [ 32 ], medical education [ 33 ], community-based housing [ 34 ], health care management [ 35 ] and understanding health care access barriers [ 36 ], among others. Traditionally, concept mapping is done over a series of steps or stages using tools such as paper, posters, post-it-notes and markers to engage groups in the process of cooperative conceptualization.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, different societies may also place more or less weight on the various psychological, physiological, and social aspects of ageing, based on the local socio-cultural environment (Bowling, 2007; Young et al ., 2009; Fernandez-Ballestros et al ., 2010; Reichstadt et al ., 2010; Lewis, 2014; Ahn et al ., 2017; Tkatch et al ., 2017; Black and Hyer, 2019; Chen et al ., 2019). Since there is clearly a great degree of variation between how different groups of people define healthy ageing, there remains a need to create local holistic models of healthy ageing in socio-cultural context that engage a variety of stakeholders (Soellner et al ., 2017; Howell et al ., 2020; Trevino et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because CM is often used for conceptualising both the nature of difficult health problems and methods to resolve them (Trochim and Kane, 2005), this method is well-suited for the investigation of how stakeholders perceive importance and feasibility of healthy ageing in their community through a participatory framework (Rosas, 2012; Vaughn et al ., 2017). We utilised CM to define healthy ageing in Anchorage, Alaska in our previous work (Howell et al ., 2020) and here we present further usage of CM to elicit the importance and feasibility of 12 components of healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation